Pengaruh Jenis Larutan Pemasak Terhadap Kualitas Pulp Daun Pisang - Risnita Vicky Listyarini; Noer Kurnia Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
The need for paper continues to increase, indicating that there is an alternative wood material that can be used as a base for making pulp. Materials that can be used are dried banana leaves which contain cellulose. The quality of the pulp can be obtained by the characteristics of the pulp produced. This study was conducted to determine the effect of the type of solvents on the pulp quality of banana leaves. The pulp has been made using delignification process with addition of 3% NaOH or 3% Na2CO3 3% and heating up to 120 minutes, at 105 Ã‚Â°C. Pulp quality was obtained from the results of pulp analysis, cellulose content, water content, physical appearances and qualitative analysis by FTIR. From the analysis of cellulose content, water content and FTIR instruments, pulp made with 3% NaOH solution are better suited to 3% Na2CO3 where the resulting pulp has a water content of 4.96%, a smooth and fibrous texture, a rich color, and produces a cellulose hydroxyl absorption band that is stronger than the pulp made of 3% Na2CO3. However, the pulp made from 3% NaOH solution has a lower yield (56.5%) and cellulose content (26.07%) than Na2CO3 3%. Dried banana leaves can be used as an alternative in pulp making. Keywords: pulp making; banana leaves; solvents